Constitutive activation of the fucAO operon and silencing of the divergently transcribed fucPIK operon by an IS5 element in Escherichia coli mutants selected for growth on L-1,2-propanediol. - Chen, Y M (1989)
L-1,2-Propanediol is an irretrievable end product of L-fucose fermentation by Escherichia coli. Selection for increased aerobic growth rate on propanediol results in the escalation of basal synthesis of the NAD+-linked oxidoreductase encoded by fucO, a member of the fuc regulon for the utilization of L-fucose. In general, when fucO becomes constitutively expressed, two other simultaneous changes occur: the fucA gene encoding fuculose-1-phosphate aldolase becomes constitutively expressed and the fucPIK operon encoding fucose permease, fucose isomerase, and fuculose kinase becomes noninducible. In the present study, we show that fucO and fucA form an operon which is divergently transcribed from the adjacent fucPIK operon. In propanediol-positive and fucose-negative mutants the cis-controlling region shared by the operons fucAO and fucPIK is lengthened by 1.2 kilobases. DNA hybridization identified the insertion element to be IS5. This element, always oriented in the same direction with the left end (the BglII end) proximal to fucA, apparently causes constitutive expression of fucAO and noninducibility of fucPIK. The DNA of the fucAO operon and a part of the adjacent fucP was sequenced.